Polymorphism and allelic frequency of CSN1S1 in different cattle breeds in Bulgaria - Yordanova, Daniela; Angelova, Teodora; Karabashev, V.; Kalaydhziev, Georgi; Laleva, Stayka; Cassandro, Martino; Maretto, F.; Krastanov, Jivko; Popova, Yovka; Oblakov, N. (Acta Agraria Kaposváriensis, 2014)
The present study aims at determining the genetic polymorphism at the milk protein genes CSN1S1 and their allelic frequency in widespread and endangered cattle breeds raised in Bulgaria. Analyzed were 390 tissue samples of two widespread cattle breeds, i.e. 129 of the Bulgarian Brown Cattle and 129 of the Bulgarian Black and White Cattle, as well as of two endangered cattle breeds- 23 of the Rhodopean Short - Horned Cattle and 109 of the Iskar Cattle. Determined are significant differences in the frequency of the heterozygous genotypes, i.e. higher frequency in the local breeds. The Iskar Cattle stands out with the highest percentage of the BC heterozygous genotype, i.e.- 66.972% compared to the other breeds included in our study.